FAAS determination of metal nutrients in fish feed after ultrasound extraction - Neves, Renato C. F. [UNESP]; Moraes, Paula M. [UNESP]; Saleh, Mayra A. D. [UNESP]; Loureiro, Vanessa R. [UNESP]; Silva, Fabio A. [UNESP]; Barros, Margarida Maria [UNESP]; Padilha, Cilene C. F. [UNESP]; Jorge, Sonia M. A. [UNESP]; Padilha, Pedro de Magalhães [UNESP] (Elsevier B.V., 2009)
This paper proposes a method to determine calcium, magnesium, manganese and zinc in fish feed samples using ultrasound in the analyte extraction process, and subsequent quantification by flame atomic absorption spectrometry (FAAS). Using 0.10 mol/L of HCl as extraction solution, the optimal conditions of extraction were established as follows: 100 mg of sample mass; sample granulometry of less than 60 pm; sonication time of three cycles of 10 s and sonication power of 102 W. The method was applied in Studies of the digestibility of these nutrients in samples of fish feed used in the diet of Nile tilapia juveniles. The results achieved were congruent with those obtained from the mineralization of fish feed samples in the metal nutrient extraction process. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Fish nutrition; Absorption of metal nutrients; Ultrasound; FAAS